(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: To determine maternal and perinatal outcomes in patients with antepartum eclampsia in a tertiary care hospital. Study Design: Design Prospective observational study. Place and Duration of Study: Department of Obstetrics and Gynaecology, Jinnah Postgraduate Medical Centre (JPMC), Karachi from 1st October 2024 to 31st March 2025. Methodology: A cross-sectional study was conducted: 189 antepartum eclampsia diagnosed pregnant women were recruited through non -probability consecutive sampling. ICU admissions, length of ICU stay, maternal mortality and causes, recurrence of seizures after magnesium sulphate, fetal outcomes, Apgar scores and birthweight. Statistical analyses were conducted with SPSS version 25. Results: 84% of 189 patients needed ICU admission. There was maternal mortality in 18% and cardiopulmonary failure (92.6%) was the main cause. There was a history of recurrent epileptic fits in 16% of patients. Stillbirths were 43.4%, neonatal deaths 13.8%, and Apgar score of <7 at 5-min were observed in 57.1% of neonates. Mean birthweight was 2.24 kg. Conclusion: Poor maternal and fetal outcomes are related to antepartum eclampsia. Early diagnosis, increasing the quality of antenatal care and consolidation of specialized intensive care must be provided to decrease mortality and improve the prognosis. Objective: To determine maternal and perinatal outcomes in patients with antepartum eclampsia in a tertiary care hospital. Study Design: Design Prospective observational study. Place and Duration of Study: Department of Obstetrics and Gynaecology, Jinnah Postgraduate Medical Centre (JPMC), Karachi from 1st October 2024 to 31st March 2025. Methodology: A cross-sectional study was conducted: 189 antepartum eclampsia diagnosed pregnant women were recruited through non -probability consecutive sampling. ICU admissions, length of ICU stay, maternal mortality and causes, recurrence of seizures after magnesium sulphate, fetal outcomes, Apgar scores and birthweight. Statistical analyses were conducted with SPSS version 25. Results: 84% of 189 patients needed ICU admission. There was maternal mortality in 18% and cardiopulmonary failure (92.6%) was the main cause. There was a history of recurrent epileptic fits in 16% of patients. Stillbirths were 43.4%, neonatal deaths 13.8%, and Apgar score of <7 at 5-min were observed in 57.1% of neonates. Mean birthweight was 2.24 kg. Conclusion: Poor maternal and fetal outcomes are related to antepartum eclampsia. Early diagnosis, increasing the quality of antenatal care and consolidation of specialized intensive care must be provided to decrease mortality and improve the prognosis.